Micro-Movement Measured by Laser Heterodyne Interferometer Based on Acousto-Optic Effect - Lin, Bailin; Dai, Wei; Sun, Jun; Xiao, Mengting; He, Zihan; Wu, Jianjian; Chen, Xinqi (Frontiers in Physics, 2022)
In this experiment, the stable output of a dual-frequency laser source is obtained by an acousto-optic modulator due to the Bragg diffraction effect. Furthermore, the non-polarized dual-laser heterodyne interferometer is designed to measure the micro-movement of stacked PZT piezoelectric ceramic. This micro-movement can be dynamically determined by comparing the phase difference between the conference beam and measuring beam. The results indicate that the micro-movement of PZT piezoelectric ceramic changes linearly with the driven-voltage in the range of 0-30 V and the sensitivity of movement to voltage is 58.3 nm/V, which is very close to the theoretical value and this laser heterodyne interferometer can be applied for calibrating parameters of piezoelectric ceramic.